Reinvesting the cellular properties of human amniotic epithelial cells and their therapeutic innovations - Yang, Jing; Lu, Yuefeng; Zhao, Jinping; Luo, Yi; Hao, Wangping; Zhang, Wencheng; He, Zhiying (Frontiers in Immunology, 2024)
Human amniotic epithelial cells (hAECs) have shown promising therapeutic effects in numerous studies on various diseases due to their properties such as low immunogenicity, immunomodulation, paracrine effect, and no teratoma formation in vivo. Nevertheless, there are still many problems in archiving the large-scale clinical application of hAECs, ranging from the vague definition of cell properties to the lack of clarification of the motion of actions in cell therapies, additionally, to the gap between cell quantities with limited proliferation capacity. This review provides a detailed overview of hAECs in the aspects of the lineage development of amniotic epithelial cell, cell characteristics and functional roles, ex vivo cell cultivation and expansion systems, as well as their current status and limitations in clinical applications. This review also discusses the advantages, limitations and feasibility of hAECs, and anticipates their prospects as cell therapy products, with the aim of further promoting their clinical applications.